Peningkatan Literasi, Numerasi, Adaptasi Teknologi, Administrasi Sekolah dan Softskill dalam Program Kampus Mengajar di SD Negeri Polaman, Kecamatan Mijen, Kota Semarang - Wahyuni Arumsari; Agita Tri Cahyani; Anggie Monica; Nida Hudani Sabila; Hana Zhafirah; Eka Nur Amalia Septianingsih; Stepvani Iqbal Kurnia Setia Budi (Jurnal Surya Masyarakat, 2022)
Kampus Mengajar Programe was initiated by kementrian Pendidikan, Kebudayaan, Riset dan Teknologi (Kemendikbud Ristek) as a program that offers opportunities for students from all study program backgrounds throughout Indonesia to contribute in the field of education. In addition to getting an off-campus learning experience, selected students are entitled to a conversion of 20 credits. A total of six students and one field supervisor (DPL) were assigned to SD Negeri Polaman in Mijen District, Semarang City with B accreditation. Program implementation methods that have been implemented include: initial assessment, implementation of activities (literacy and numeracy assistance, adaptation technology, school administration, and soft skills improvement) and final assessment. The results of this program include improving services in terms of teaching (literacy and numeracy), the use of technology for students and teachers, structuring school administration, and improving soft skills for students. Based on this programe, it can be concluded that this program has a positive impact on various parties, including schools, students, and  also DPL.